Characterisation of plant growth-promoting bacteria from Kacip Fatimah (Labisia pumila) under natural tropical forest - A., Yasmi; Othman, Radziah; Jaafar, Hawa Z. E.; Mior Ahmad, Zainal Abidin; Panhwar, Qurban Ali (Universiti Putra Malaysia Press, 2016)
Medicinal plants play a major role in many cultures, not only as medicines, but also as trade commodities to fulfil the demands of distant markets. A study was conducted to characterise growth-promoting bacteria from two varieties of Kacip Fatimah (Labisia pumila) found at two different locations, Sungai Tekala, Semenyih, Selangor for Labisia pumila var. lanceolate and Bukit Slim Permanent Forest Reserve, Perak for Labisia pumila var. alata. Soil and plant samples were taken for the physico-chemical analyses and characterisation of the indigenous plant growth-promoting bacteria (PGPB). Both Labisia varieties were found to thrive in areas with quite similar soil chemical and physical properties in natural forest environments except for altitude, where Labisia pumila var. alata was found in higher elevation compared to Labisia pumila var. lanceolata. The soil in both places was found to be slightly acidic and low in nutrient content. Total bacterial population found on var. alata was higher than in var. lanceolata and the highest population was found in the root endosphere (8.68 × 107 cfu g-1 soil). Morphologically-isolated bacteria were circular in shape, with flat/raised elevation, entire margin, moist texture and smooth and glistening surface but varied in colour and size. Most of the bacterial strains showed several plant-growth promoting traits like plant-growth hormones (indole acetic acid (IAA)), N2 fixation and P solubilisation activities and beneficial enzymes. Two of the bacterial isolates showing most of the beneficial properties were identified as Exiguobacterium sp. and Stenotrophomonas sp. These PGPB have the potential to enhance the growth of Kacip Fatimah.